The First Serbian Translation of Plato’s Apology - Deretić, Irina J.; Ristevski, Aleksandar D. (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
In this paper, we will critically assess the philosophical and linguistic aspects of the first Serbian translation of Plato’s Apology, that has been recently discovered. The Apology was translated by Kosta J. Lozanić in 1904. First, we will analyze the philosophical terminology of this translation, taking into account some importantpassages of the dialogue. By comparing and contrasting Lozanić’s translation with the most prominent translations of the Apology of his time, we explicate the uniqueness of his translation, that rests on the translator’s own understanding of both the Greek text and Plato’s philosophy.
Keywords: Kosta J. Lozanić; Plato’s Socrates; the divine; consciousness; control